PENDIDIKAN AGAMA ISLAM DALAM KELUARGA PEKERJA PENGRAJIN ROTAN DI KELURAHAN BALEARJOSARI KECAMATAN BLIMBING KOTA MALANG - Didit Prasetyo; Anwar Sa’dullah; Ahmad Syamsu Madyan (VICRATINA, 2020)
This research aims to describe the implementation of Islamic religious education in the families of rattan craftsmen workers in Balearjosari Sub-District, Blimbing District, Malang City and identify supporting and inhibiting factors in implementing Islamic religious education.  Against the background of busy parents in work and on the other hand have the responsibility for Islamic religious education in children. Research data collection using interview, observation and documentation methods.  Likewise, the analysis of research data uses qualitative descriptive method, which is interpreted with descriptive explanations into conclusions related to Islamic religious education in the families of rattan craftsmen workers in Balearjosari Village, Blimbing District, Malang City. Based on the results of the study, it was concluded that Islamic religious education in the families of rattan craftsmen workers who mostly applied the democratic educating model that was free but remained controlled.  The aspects that influence the implementation of Islamic religious education in the families of rattan craftsman workers can be seen from parents 'perceptions about Islamic religious education in children, forms of Islamic religious education in children and parents' targets about Islamic religious education which are generally parents.  provide the best education for their children, especially Islamic religious education.  Supporting factors and obstacles to education in the families of rattan craftsman workers are divided into two namely external factors and internal factors.  Internal supporting factors are effectiveness in communication, freedom to children with a belief.  External supporting factors are the social environment and internet usage.  Internal inhibiting factors are parental education and a lack of parental free time.  External inhibiting factors are mobile games and promiscuity.